Root yield and reserpine content of Rauvolfia serpentina Benth. on media under the plant with potential allelopathic effect by nutrient addition - SULANDJARI SULANDJARI (Society for Indonesian Biodiversity, 2008)
The root of Rauvolfia serpentina Benth (pule pandak) contains more than 50 kinds of alkaloid which is useful to treat many kinds of diseases and reserpine is ones to treat of hypertension. Eucalyptus deglupta and Acacia mangium have become release an allelochemy to ecosystem that are can reduce the growth of the plant association. The purpose of this research is to know about the influence of nutrient and media under the plant with potential allelopathic effect to root yield and reserpine content. The research was arranged in CompleteRandom Block Design. Nutrient was nested on media. Media are: under Tectona grandis, A. mangium, and E. deglupta. Nutrient is 30 t ha-1 organic fertilizers, 200 ha-1 inorganic (NPK) fertilizers and control. Polybag with 30 cmx30 cm plant densities and 20% of shading. The result are that beside under the T. grandis, pule pandak was capable to growth under the A. mangium and E. deglupta. Thirty ton per hectare organic fertilizers was increased of growth and yield more than 200 ha-1 inorganic (NPK) fertilizers. Allelocemy from A. mangium and E. deglupta was decreased dry root yield but was not effect to reserpine content.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKeywords: nutrient, Rauvolfia serpentina, reserpine, root yield.